What factors predict the confidence of palliative care delivery in long‐term care staff? A mixed‐methods study. (10th December 2019) - Frey, Rosemary; Balmer, Deborah; Robinson, Jackie; Boyd, Michal; Gott, Merryn
Abstract: Background: Research has indicated that clinical staff in long‐term care often lack self‐confidence in palliative care delivery, particularly at the end of life. Goals: (a) To examine the contribution of age, palliative care education, palliative care work‐related experience and psychological empowerment to palliative care delivery confidence and (b) to explore the social reality shaping those factors for long‐term care staff. Design: Explanatory sequential design. Setting: Twenty long‐term care facilities in two district health boards in New Zealand. Participants: Phase 1:139 clinical staff. Phase 2:46 clinical staff who provided care in the last month of a residents' life. Methods: Phase 1 : Cross‐sectional survey. Phase 2: Individual semi‐structured interviews. Results: Phase 1: Previous experience (β = .319) and psychological empowerment (β = .311) contribute most to predicting an increase in palliative care delivery confidence. Phase 2: Four factors underlay palliative care delivery confidence, (a) mentorship by hospice nurses or colleagues (b) contextual factors (organisational culture, resources and experience), (c) maturity and (d) formal education. Conclusion: Organisational leadership should use multiple strategies (e.g. power‐sharing, increased opportunities for mentorship) to improve staff palliative care delivery confidence. Implications for Practice: This study adds to the literature in understanding the predictors of palliative care delivery confidence specific to long‐term care staff. The results indicate that educational interventions must be contextually appropriate to achieve sustainable improvements in palliative care confidence and ultimately in resident care at the end of life.